1997
DOI: 10.1002/(sici)1096-9861(19970908)385:4<565::aid-cne5>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

A Golgi study of the short-axon interneurons of the cell layer and inner plexiform layer of the medial cortex of the lizardPodarcis hispanica

Abstract: The medial cortex of lizards is a three-layered brain region displaying cyto- and chemoarchitectonical, connectional, and ontogenetic characteristics that relate it to the hippocampal fascia dentata of mammals. Three interneuron types located in the cell layer and ten others in the inner plexiform layer (six in the juxtasomatic zone and four in the deep zone) are described in this study. The granuloid neurons, web-axon neurons, and deep-fusiform neurons lay within the cell layer. These neurons were scarce; the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…"Typical" pyramidal neurons have a main apical dendritic shaft directed toward the pial surface of the neocortex. "Pyramidal-like" neurons show most features of a pyramidal shape (Gloor, 1997;Luis de la Iglesia and Lopez-Garcia, 1997) although they can have an apical dendrite branching close to the cell body and with different orientation in the neuropil (Vásquez et al, 2018). For example, the pyramidal-like neurons in the human cortical nucleus of the amygdaloid complex (posterior part, PCo) have a triangular cell body, two basal dendrites of a similar thickness, and one main thick dendrite emerging at the apex of the soma.…”
Section: The Morphological Heterogeneity Of Pyramidal Neuronsmentioning
confidence: 99%
“…"Typical" pyramidal neurons have a main apical dendritic shaft directed toward the pial surface of the neocortex. "Pyramidal-like" neurons show most features of a pyramidal shape (Gloor, 1997;Luis de la Iglesia and Lopez-Garcia, 1997) although they can have an apical dendrite branching close to the cell body and with different orientation in the neuropil (Vásquez et al, 2018). For example, the pyramidal-like neurons in the human cortical nucleus of the amygdaloid complex (posterior part, PCo) have a triangular cell body, two basal dendrites of a similar thickness, and one main thick dendrite emerging at the apex of the soma.…”
Section: The Morphological Heterogeneity Of Pyramidal Neuronsmentioning
confidence: 99%
“…1D) have shown that the principal neurones are long axon projection neurones with spiny bipyramidal and ''double bouquet'' bitufted dendritic trees (De la Iglesia and Lopez-Garcia 1997a). On the other hand, interneurons located in the plexiform layers are short axon neurones with non-spiny or sparsely spiny dendrites displaying diverse morphologies , (De la Iglesia and Lopez-Garcia 1997b, Bernabeu et al 1994. Most local interneurons are GABA-immunoreactive (Lopez-Garcia et al 1988 a, Schwerdtfeger and and display either parvalbumin (Fig.…”
Section: The Cerebral Cortex Of Reptilesmentioning
confidence: 99%
“…Nevertheless, that nomenclature appears somewhat confusing, because we have found in Podarcis some short-axon interneurons displaying pyramidal-like shaped cell bodies (Luis de la Iglesia and Lopez- Garcia, 1997).…”
Section: Heterogeneity Of the Lizard Medial Cortex Projection Neuronsmentioning
confidence: 99%
“…The plexiform layers are made up of the principal cell dendrites intermingled with the incoming axons, the radial glial scaffold, and a reduced population of isolated cells, including solitary neurons, and microglia-like cells. Short-axon neurons of the medial cortex plexiform layers, although scarce, are very heterogeneous; up to five intrinsic neuronal types have been identified in the outer plexiform layer of this lizard species (Luis de la , and up to 19 types of presumably interneurons may be distinguished in the inner plexiform layer of the same species (Luis de la Iglesia, 1995; Luis de la Iglesia and Lopez- Garcia, 1997). Most of these interneurons are g-aminobutyric acid (GABA) immunoreactive (Schwerdtfeger and Lopez-Garcia, 1986;Schwerdtfeger and Lorente, 1988a,b), and also display diverse neuropeptide immunoreactivity (Martínez-Guijarro et al, 1993), calcium binding protein immunoreactivity (Martínez-Guijarro et al, 1991b, 1993Martínez-Guijarro and Freund, 1992a), and even nicotinamide adenine dinucleotide phosphate (NADPH diaphorase) activity (Regidor and Poch, 1988;Dá vila et al, 1995).…”
mentioning
confidence: 99%